THE RELATIONSHIP BETWEEN PROCRASTINATION AND CREATIVE THINKING - Rumyantseva, Katerina; Movchan, Larysa (Scientific Journal of Polonia University, 2022)
The article considers the issue of the relationship between the phenomenon of procrastination and creative thinking. One of the most common factors that hinder personal and professional effectiveness is procrastination. There is a hypothesis that people with high levels of procrastination have correspondingly well-developed creative thinking, which endows them with the ability to solve problems outside the box and quickly adapt to situations.1 We consider procrastination as a psychological pattern of behavior characterized by person’s delaying planned actions or decision-making followed by negative emotional experiences. Literature analysis has shown that procrastination influences creative activity, which leads to the assumption that people with higher levels of procrastination have a higher level of creativity. Upon conducting our research, we uncovered the following pattern: students with a high level of procrastination are more inclined to such factors as risk-taking and fantasy; students with a low level are more likely to present curiosity and task complexity; and students with an average level of procrastination are equally likely to present both factors.